Quality control of the connections with the interference, assembled by the thermal method - Зенкін, Анатолій Семенович; Оборський, Іван Леонідович (Eastern-European Journal of Enterprise Technologies, 2011)
Work examines questions of study and control of strength of the connections with the interference, assembled by thermal method, on the acoustic and frequency- thermal parameters